The effects of margin changes on commodity futures markets - Charoula Daskalaki; George Skiadopoulos (Queen Mary University of London, School of Economics and Finance, 2014)
In light of the recently passed 2010 Dodd-Frank Act, we assess the effect of margin changes on prices, the risk-sharing between speculators and hedgers, and the price stability of 20 commodity futures markets. We find that margin increases decrease the rate at which prices change, yet they impair the risk sharing function and they decrease market liquidity in certain markets. The regulator should set margins by taking the heterogeneity of commodity futures markets into account. Certain effects of margin changes diffuse across related markets though. Our results are robust to endogenously set margins by the exchanges.
Keywords: G10; G14; G18; G28; 330; Commodities; Hedging; Market liquidity; Margins; Speculators